QUALITY STANDARDS FOR BAKERY PRODUCTS FOR CHILDREN’S INSTITUTIONS: ANALYSIS OF REGULATORY REQUIREMENTS AND PRACTICAL RECOMMENDATIONS FOR MANUFACTURERS - Korniienko, Anastasiia (Global Prosperity, 2026)
The article is devoted to the systematization of the regulatory and legal framework of Ukraine regarding the quality and safety of bakery products for children’s educational institutions and the development of practical quality control methods for small baking enterprises. The purpose of the study is to analyze the current requirements and formulate recommendations that can be directly implemented in production without significant capital expenditures. Methods of regulatory analysis, synthesis and comparison, a structural-functional approach, as well as practical technological modeling based on the practical production observations were used. It has been established that bakery products for school cafeterias are subject to significantly stricter parameters than general standards: salt content - no more than 0.45 g/100 g, sugars - no more than 5 g/100 g, with a mandatory base of rye or whole grain flour (Appendix 9 to Sanitary Regulations No. 2205, last edition 01.01.2026). The author’s methodology is based on five critical control points of the HACCP system – from incoming flour control to regulated cooling before packaging – and can be implemented in small facilities with minimal equipment. Six typical mistakes made by manufacturers that systematically lead to quality instability have been identified: salt dosing without weighing, lack of temperature logging of fermentation, acceptance of flour without incoming inspection, ignoring the sanitary condition of surfaces, lack of production documentation, and premature packaging. The practical value of the results lies in their direct applicability to small enterprises that supply bread to preschool and general secondary education institutions.